2019
DOI: 10.2136/vzj2018.11.0196
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Biopores on Root Growth and Root Water Uptake

Abstract: Core Ideas A 3D soil–root model was used to investigate root–biopore interactions. Known effects of biopores on root growth, i.e., increased root length and depth were reproduced. Despite reducing root–soil contact, biopores led to increased water uptake in dry periods. Biopores had a larger impact on water uptake for more compact and less conductive soils. Roots are known to use biopores as preferential growth pathways to overcome hard soil layers and access subsoil water resources. This study evaluates roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 89 publications
1
19
0
1
Order By: Relevance
“…These results are in accordance with Foloni et al (2006), who concluded that an increase in soil penetration resistance in the surface layer could stimulate lateral root proliferation, which is thinner and capable of growing in small diameter soil pores, reaching higher depths. It occurs especially in consolidated no-tillage areas, where there is the natural formation of biopores that allows for higher root growth and, consequently, access to water in deeper and wetter soil layers, mainly in those more compact and less conductive (Landl et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These results are in accordance with Foloni et al (2006), who concluded that an increase in soil penetration resistance in the surface layer could stimulate lateral root proliferation, which is thinner and capable of growing in small diameter soil pores, reaching higher depths. It occurs especially in consolidated no-tillage areas, where there is the natural formation of biopores that allows for higher root growth and, consequently, access to water in deeper and wetter soil layers, mainly in those more compact and less conductive (Landl et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Landl et al . (2019) used a coupled root growth model and water uptake model to determine the role of biopores on RSA and water uptake. Schnepf et al .…”
Section: Introductionmentioning
confidence: 99%
“…One opportunity for roots to overcome compacted soil layers is the use of large-sized biopores formed by tap-rooting plants or earthworms as preferential growth pathways (Kautz et al, 2014;Landl et al, 2019;Huang et al, 2020). Biopores are hotspots with particularly high organic matter, microbial activity and nutrient availability (Kautz et al, 2014;Kuzyakov and Blagodatskaya, 2015), which enhance water infiltration and have a proven beneficial impact on root water uptake in times of drought (Gaiser et al, 2012;Landl et al, 2019). These biopores can remain in the subsoil over years (Hagedorn and Bundt, 2002).…”
Section: Alfalfa Cultivationmentioning
confidence: 99%
“…There are various mechanical and biological methods that help overcome such compacted soil layers, facilitate root growth into deeper layers (Schneider and Don, 2019b) and thus support the uptake of nutrients and water from the subsoil-and thereby increase yields (Gaiser et al, 2012;Cai et al, 2014;Landl et al, 2019;Sale et al, 2019;Seidel et al, 2019). Biological methods are based on the effect of the cultivation of deep-rooted precrops (e.g., alfalfa) and the formation of biopores down into the subsoil (bio-drilling) (Kautz et al, 2014;Landl et al, 2019;Seidel et al, 2019). Mechanical methods encompass for example deep loosening (subsoiling) to break up compacted layers (Frelih-Larsen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%